Characterizing patients with psoriasis on injectable biologics adalimumab, etanercept, and ustekinumab: A chart review study. (3rd July 2016) - Zhang, Mingliang; Goren, Amir; Lee, Seina; DiBonaventura, Marco D.; Olson, William H.
Abstract: Objective : This study examined plaque psoriasis (PsO) patient characteristics across injectable biologics. Methods : Data were collected from 400 US dermatologists randomly selecting five charts each for patients with PsO (patient n  =  2000): adalimumab (ADA; n  =  447), etanercept (ETA; 539), ustekinumab (UST) 45 mg (511) and UST 90 mg (503). Physicians had to have been in practice 2–30 years, managing 10+  patients (5 + with biologics for PsO). Generalized estimating equation models, weighted according to inverse probability of patient selection and accounting for patient correlation within physicians, examined patient measures as a function of treatment (UST 90 mg = reference). Results : Patients on UST 90 mg had higher odds of weighing  >100 kg (adjusted mean  =  34.4%) vs. ADA (10.9%), ETA (5.5%) or UST 45 mg (6.8%), greater body surface affected and higher odds of severe PsO prior to treatment and higher odds of prior biologics use. Mean prior biologics used was higher with UST 90 mg versus ADA or ETA. Number of comorbidities was higher with UST 90 mg versus ETA or UST 45 mg. Conclusions : Among biologics-treated patients with PsO, UST 90 mg appears to be used in patients with greater weight, baseline severity and prior biologics experience than ADA, ETA or UST 45 mg. UST 90 mg is used in patients with more comorbidities than other treatments except ADA.